Використання комп’ютерних ігор для зниження стресового стану людини у воєнний час - Коноваленко, Д. О. (ХНУРЕ, 2024)
During military conflicts, computer games can play an important role in alleviating stress among civilians. Civilians experiencing military conflict can use computer games to distract themselves from stressful situations and find moments of relaxation.
Keywords: комп’ютерна гра; зниження стресового стану; воєнний час